Effects of Blended Learning in Comparison of Traditional Learning to Provide Safer Learning Environment- A Comparative Review - Hafeez, Muhammad; Akhter, Yasmeen (CV. Inara, 2021)
Learning strategies have shifted from conventional information to communication technology-based learning since the beginning of the twenty-first century. A study of published articles on blended and traditional learning strategies was done to emphasise the value and significance of both learning strategies and to investigate their efficacy in promoting a safer learning environment in different educational levels. Thirty-six (36) research articles from various disciplines published in Web of Science and Scopus databases were chosen for review. According to the review of researches, blended learning demonstrated to be a more successful learning approach than traditional learning strategy in the majority of studies. Twenty-five (25) studies found a statistically more significant benefit in blended learning strategy for academic success, critical and creative abilities, and a safer learning environment in diverse disciplines, out of 36 published articles evaluated. Based on the findings of this study, it is strongly suggested that blended learning strategies be used to attain high academic and professional goals while also providing a safer learning environment in educational institutions and society.